2017
DOI: 10.1002/2017jg003780
|View full text |Cite
|
Sign up to set email alerts
|

Shallow ponds are heterogeneous habitats within a temperate salt marsh ecosystem

Abstract: Integrating spatial heterogeneity into assessments of salt marsh biogeochemistry is becoming increasingly important because disturbances that reduce plant productivity and soil drainage may contribute to an expansion of shallow ponds. These permanently inundated and sometimes prominent landscape features can exist for decades, yet little is known about pond biogeochemistry or their role in marsh ecosystem functioning. We characterized three ponds in a temperate salt marsh (MA, USA) over alternating periods of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
86
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(96 citation statements)
references
References 89 publications
(115 reference statements)
8
86
1
1
Order By: Relevance
“…Long stretches of hydrologic isolation facilitate the accumulation of metabolites and depletion of critical resources (e.g., inorganic nutrients), thereby altering pond biogeochemistry. Tidal flushing may only partially alleviate these effects because exchange is often incomplete (Spivak et al ). Ponds also differ from other coastal habitats because they are embedded in the marsh platform and surrounded by organic‐rich peat.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Long stretches of hydrologic isolation facilitate the accumulation of metabolites and depletion of critical resources (e.g., inorganic nutrients), thereby altering pond biogeochemistry. Tidal flushing may only partially alleviate these effects because exchange is often incomplete (Spivak et al ). Ponds also differ from other coastal habitats because they are embedded in the marsh platform and surrounded by organic‐rich peat.…”
mentioning
confidence: 99%
“…Respiration measurements suggest that decomposition of marsh peat is an important process contributing to progressive pond development (Johnston et al ; Spivak et al ). However, respiration data are scarce and reflect the combined metabolism of the animal, plant, and bacterial communities that inhabit ponds (Johnston et al ; Moseman‐Valtierra et al ; Spivak et al ). Moreover, bacteria can assimilate OM from multiple sources and decomposition rates and pathways are affected by local plant communities.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Because gas exchange from wetland ponds has rarely been measured (Moseman‐Valtierra et al, ), and no relationships were found with environmental variables measured, it is difficult to attribute GHG exchange in ponds to specific factors measured in this study. Shallow ponds in salt marsh landscapes have been described as very heterogeneous in terms of their gas exchange by Spivak et al (). Our data agree with the notion that these semi‐isolated ponds either import or export organic material (Spivak et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Shallow ponds in salt marsh landscapes have been described as very heterogeneous in terms of their gas exchange by Spivak et al (). Our data agree with the notion that these semi‐isolated ponds either import or export organic material (Spivak et al, ). Therefore, ponds in wetland landscapes—either natural or anthropogenic—should not be included in C inventory calculations until properly researched, as these ponded features are still understudied in terms of C assimilation (Spivak et al, ; Berkowitz et al, ).…”
Section: Discussionmentioning
confidence: 99%